Total kinetic energy production of body segments is different between racing and training paces in elite Olympic rowers - Bechard, D. J.; Nolte, V.; Kedgley, A. E.; Jenkyn, T. R. (Sports Biomechanics, 2009)
Total kinetic energy (TKE) was calculated for 28 Canadian national team Olympic rowers during training on water, comparing low-stroke rates (18-22 stroke/min) and high-stroke rates (32-40 stroke/min), using video analysis. Stroke duration was normalized to 100%, beginning and ending at the "catches", with the drive phase occurring first and recovery second. Two discrete points were identified during the stroke, both occurring when the fingers had the same horizontal position as the ankles (i.e. mid-drive and mid-recovery). The ratios of recovery-to-drive TKE at these points for the entire body at low and high-stroke rates were 0.36 ± 0.34 and 1.26 ± 0.54 respectively. Significant differences were found for the lower leg, upper arm and forearm segments, and within the female groups. Low-stroke rate is a typical training pace and high-stroke rate is analogous to a race pace. This study demonstrates that TKE production during recovery in a race was not replicated during training. While training at low-stroke rates is vital for technique refinement, this study stresses the importance of training appropriately for the energy expenditure during high-stroke rate recovery. This is commonly overlooked by coaches and athletes.